A Novel Update on the Management of Müller-Weiss Disease: Presentation of a Treatment Algorithm - Angthong, Chayanin; Younger, Alastair S.E.; Chuckpaiwong, Bavornrit; Harnroongroj, Thos; Veljkovic, Andrea (My University, 2024)
Objective: Müller-Weiss disease (MWD) is a challenging condition involving the perinavicular region in the initial stages and subsequently the entire foot in the later stages. The goal of this article is to describe the pathomechanics, clinical evaluation, and nonoperative and operative treatment, including a treatment algorithm, based on current evidence and the combined authors’ experience. Design: We review the related articles and summarize the information about this condition. Results: A number of related articles reveal that the treatments should focus on the management of degenerative regions and deformity correction to restore normal foot alignment and provide pain relief. Conclusion: This systematic review proposes a treatment algorithm that is comprehensive and practical to apply for the management of MWD.
Keywords: Müller-Weiss disease; navicular bone dysplasia; pathomechanics; surgical treatment